Varicella gangrenosa. Issue 4 (April 1988) - Kidney, D D; Watson, J B; Nisar, N
Abstract : A four year old girl presented with varicella gangrenosa, and haematological investigations showed a disseminated intravascular coagulation. The child subsequently developed a unilateral deep venous thrombosis. She was treated with oral steroids and intravenous heparin and made a full recovery.